PERANAN KOMISI PERLINDUNGAN ANAK INDONESIA DALAM MEMBERIKAN PERLINDUNGAN HUKUM TERHADAP ANAK KORBAN TINDAK PIDANA PENGANIAYAAN (STUDI KASUS: PENGANIAYAAN ANAK ADOPSI DI HOTEL LE MERIDIEN JAKARTA PUSAT OLEH CW) - Sherly Livinus; Mety Rahmawati (Fakultas Hukum Universitas Tarumanagara, 2018)
So many of the phenomenon of violence and crime against children become the harsh spotlight from various circles. Pursuant to Article 20 of Law Number 23 Year 2002 regarding Child Protection, the State, Government, Society, Family and Parents shall be responsible and responsible for the implementation of child protection. The purpose of this study is to look at one of the state institutions established by the government, the Indonesian Child Protection Commission (KPAI) in providing protection for children victims of violent crime. The author took one example of a case study of violent crime against children considering that until now still often occur. The results indicate that there are various efforts by the Indonesian Child Protection Commission (KPAI) to provide legal protection against victims of crime, such as monitoring the progress of the ongoing case and cooperating with community-formed institutions in the field of child protection to realize the welfare of children without discriminatory treatment in order to grow, develop optimally, physically, mentally, and socially.